Are there differences between men and women in outcome of intensive inpatient treatment for anorexia nervosa? An analysis of routine data. (20th July 2018) - Voderholzer, Ulrich; Hessler, Johannes Baltasar; Naab, Silke; Fichter, Manfred; Graetz, Alexander; Greetfeld, Martin; Heuser, Jörg; Schlegl, Sandra
Abstract: Objective: Anorexia nervosa (AN) in men is rare and understudied. We compared admission characteristics and response to specialized inpatient treatment between men and women with AN. Method: One hundred sixteen consecutive male patients with AN were matched to 116 female patients. Patients completed the self‐rating Structured Inventory for Anorexic and Bulimic Syndromes (SIAB‐S) at admission and discharge. Differences at admission and in treatment response were examined with independent samples t ‐tests and ANOVA for repeated measures, respectively. Results: Men had lower body mass index (BMI)‐percentiles (Cohen's d  = −0.55), higher levels of weight suppression ( d  = 0.65), and higher scores in the SIAB‐S general psychopathology and social integration scale ( d  = 0.47) at admission. There were no differences in response to treatment except for changes in BMI‐percentile ( F  = 4.49, p  = 0.035). Conclusions: There were more similarities than differences between genders in AN. Because this similarity might be confounded with traditionally "feminine" conceptualizations of AN, further studies of male AN are needed.